2015
DOI: 10.1007/s00795-015-0130-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased phosphorylation of ERK1/2 is associated with worse chemotherapeutic outcome and a poor prognosis in advanced lung adenocarcinoma

Abstract: Constitutive activation of extracellular signal-regulated kinase (ERK)1/2 pathway, that is activated by various stimuli including growth factors and oncogenic driver mutations, is observed in various cancers. However, the difference of the activated levels of the pathway is still unclear in clinical significances. The aim of this study was to investigate the effect of different ERK1/2 pathway activation, assessed by the expression levels of phosphorylated (p) ERK1/2, on the prognosis of advanced lung adenocarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…Signatures. KRAS activates ERK signaling (1,3,29). KRASpositive vs. -negative lung tumors were found to exhibit ERK2 vs. ERK1 activation ( Fig.…”
Section: Kras-positive Vs -Negative Tumors Exhibited Unique Erk Proteinmentioning
confidence: 93%
“…Signatures. KRAS activates ERK signaling (1,3,29). KRASpositive vs. -negative lung tumors were found to exhibit ERK2 vs. ERK1 activation ( Fig.…”
Section: Kras-positive Vs -Negative Tumors Exhibited Unique Erk Proteinmentioning
confidence: 93%
“…Conversely, a study in patients with non-small cell lung cancer observed that higher levels of cytoplasmic p-AKT had a trend toward longer overall survival; whereas higher levels of nuclear p-AKT had a poorer prognosis [93]. In general, investigators have identified an association between ERK activation and poor prognosis such as aggressive neoplastic features, metastasis, and reduced survival [94,95]. In a study among breast carcinoma patients, p-ERK was shown to be associated with higher TNM stage and lymph node metastasis [96].…”
Section: Leptin Biology and Molecules Of Relevant Signal Transductmentioning
confidence: 99%
“…Researchers have been identifying prognostic biomarkers in tumor patients. Proteins such as vascular endothelial growth factor A (VEGF-A) [6], extracellular signal-regulated kinase (ERK) [7], matrix metalloproteinases (MMPs) [8], and pro-apoptotic protein p53 [9] were found to be associated with the overall survival time of patients and the malignant behaviors of some tumors. However, it is still necessary to explore established markers possessing predicative values for the survival of cancer patients.…”
Section: Introductionmentioning
confidence: 99%